The Relationship Between Age, Parity And History Of Abortion With The Incidence Of Abortion At RSU Ummi Bengkulu Year 2024 - Fitriyani, Fitriyani; Saputri, Meita Tria; Putri, Yesi (Universitas Dehasen Bengkulu, 2025)
In 2017 there were 20 million cases of abortion in the world each year and 70,000 women died from abortion each year. Abortion cases in Southeast Asia amount to 4.2 million per year. In Indonesia, the incidence of abortion is 10-15% of 6 million pregnancies each year or 600,000-900,000. Artificial abortion is ± 750,000-1.5 million annually, 2,500 of which end in death (World Health Organization, 2020). Based on an initial survey that was conducted in December at Ummi Bengkulu Hospital, there were 20 pregnant women who experienced abortion, pregnant women with ages <20 years and >35 years were 3 (15%), pregnant women with parity 1 and more than >3 were 5 (25%), pregnant women with age >35 years parity >3 have a history of abortion amounted to 3 (15%), pregnant women with age >35 years parity >3 amounted to 2 (10%), pregnant women with parity >3 have and history of abortion amounted to 1 (5%), pregnant women with age 20-35 years parity 2-3 do not have a history of abortion amounted to 3 (15%). The method used in this study is quantitative, namely research used to determine the relationship between two variables with a longitudinal study approach. Univariate results A small proportion of abortions have age at risk, a small proportion of abortions occur in primiparous, multiparous pregnancies and most in multiparous rande pregnancies, a small proportion of pregnancies with a history of abortion, most have pregnancies without a history of abortion. bivariate results There is a significant conclusive relationship with abortion at Ummi Hospital bengkulu in 2024. In order to make input to pregnant women, mothers should control their pregnancy by doing ANC, avoiding things that have a negative impact on pregnancy, and maintaining mental health in accordance with the provisions of the government in order to avoid the incidence of abortion in future pregnancies.